2010
DOI: 10.17221/67/2009-hortsci
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of promising apricot (Prunus armeniaca L.) genetic resources in Central Serbia based on blossoming period and fruit quality

Abstract: Milošević T., Milošević N., Glišić I., Krška B., 2010. Characteristics of promising apricot (Prunus armeniaca L.) genetic resources in Central Serbia based on blossoming period and fruit quality. Hort. Sci. (Prague), 37: 46-55.This study presents results on the performance of apricot (Prunus armeniaca L.) genotypes in Central Serbia. The research included observation and recording of biological (i.e. phenological) traits and in situ sampling of fruits from 1,210 grafted trees for determination of pomological a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
17
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 22 publications
5
17
1
Order By: Relevance
“…According to Ishag et al (2009), the TA content of fresh fruit in the apricot cultivars grown in Azad Jammu and Kashmir was 0.94%. The range of TA values obtained in this study is in agreement with the previous works on apricot (Audergon et al 1990;Mehlenbacher et al 1991;Egea et al 1997;Milošević et al 2010).…”
Section: Evaluation Of Chemical Attributessupporting
confidence: 93%
See 3 more Smart Citations
“…According to Ishag et al (2009), the TA content of fresh fruit in the apricot cultivars grown in Azad Jammu and Kashmir was 0.94%. The range of TA values obtained in this study is in agreement with the previous works on apricot (Audergon et al 1990;Mehlenbacher et al 1991;Egea et al 1997;Milošević et al 2010).…”
Section: Evaluation Of Chemical Attributessupporting
confidence: 93%
“…On the other hand, FW negatively correlated with SU content (r = -0.498). It has been reported that larger fruits have a smaller capacity to accumulate SU, as previously described by Milošević et al (2010). In general, FW was negatively correlated with SS, SS/TA ratio, RS and TS, and positively correlated with MP, Y, TA, and pH, but the correlation was not significant (Badenes et al 1998;Asma & Ozturk 2005;Hernandez et al 2010).…”
Section: Correlations Between Variablesmentioning
confidence: 72%
See 2 more Smart Citations
“…Traditionally germplasm collection and characterization had been done discribing phenological, pomological and morphological characteristics such as tree vigor and growth habit (Perez-Gonzales, 1992;Badanes et al 1998;Asma & Ozturk, 2005), fruit quality features (Rehder, 1940;Bailey & Hough, 1975;Audergon et al 1990;Souty et al 1990;Crossa-Raynaud & Audergon, 1991;Parolari et al 1992;Bassi & Bartolozzi, 1993;Badanes et al 1998;Gurrieri et al 2001;Ledbetter & Petterson, 2004;Asma & Ozturk, 2005;Ruiz & Egea, 2008;Milosevic et al 2010), leaf (Bailey, 1916;Hou, 1983;Rostova & Sokolova, 1992), stone (Felföldi et al 2009;Malik et al 2010), flower (Rodrigo et al 2006;, stigma and stylus (Viti et al 2000) and pollen (Dezhong et al 1995;Davarynejad et al 2005;Arzani et al 2005;Asma, 2008) comparing and combining the results of characaterization researches published by different groups is a difficult tusk since different variety of morphological, phenological and pomological characteristics have been assessed by the research groups. International UPOV and IPGRI criteria was created in order to overcome this unrequred situation and to enable researchers use common descriptor characteristics.…”
mentioning
confidence: 99%